2011
DOI: 10.1007/s10164-011-0316-7
|View full text |Cite
|
Sign up to set email alerts
|

Size-mediated dominance and aggressive behavior of male Japanese fluvial sculpin Cottus pollux (Pisces: Cottidae) reduce nest-site abundance and mating success of conspecific rivals

Abstract: Despite growing evidence for plasticity in the mating patterns of nest-holding animals in relation to the changes in nest abundance, the effects of aggressive interaction by dominant males on nest availability for conspecific rivals remains unclear. To quantify the effects of male-male competition on nest-site choice and mating success of the male Japanese fluvial sculpin Cottus pollux, we conducted experiments on 5 males from different 5 size classes under both sufficient and shortage nest-abundance condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This competition increases during the spawning season when a suitable shelter becomes also a nesting place. Larger males monopolize larger territories than smaller individuals, and even if a sufficient number of nesting places is provided, the dominants (larger males) prevent the smaller males approaching them through aggressive behaviour (Natsumeda 2001;Davey et al 2005;Natsumeda et al 2012). Gobies typically exhibit such territorial and aggressive behaviour (Miller 1984).…”
Section: Introductionmentioning
confidence: 99%
“…This competition increases during the spawning season when a suitable shelter becomes also a nesting place. Larger males monopolize larger territories than smaller individuals, and even if a sufficient number of nesting places is provided, the dominants (larger males) prevent the smaller males approaching them through aggressive behaviour (Natsumeda 2001;Davey et al 2005;Natsumeda et al 2012). Gobies typically exhibit such territorial and aggressive behaviour (Miller 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Japanese fluvial sculpin ( Cottus pollux ): Natsumeda et al. ) or males defending territory (e.g. in gibbons, Suwanvecho & Brockelman ).…”
Section: Introductionmentioning
confidence: 99%
“…or they may also be factors related to the species' reproductive behaviour (social behaviour, sex ratio, relative size, etc. )-all of them related to mating success in behaviour studies [42][43][44][45][46], so specific behaviour studies (ex-situ and in-situ) should be developed in order to improve captive breeding effectiveness [47]. However, it is observed that there is a limiting factor in this step.…”
Section: Analysis Of Variation Into Phasesmentioning
confidence: 99%